Studies on Turkish Hydrophilidae (Coleoptera) I. genus Enochrus Thomson, 1859 - Incekara, Ümit; Mart, Abdullah; Erman, Orhan (My University, 2005)
Two newly recorded Enochrus Thomson, 1859 (Coleoptera, Hydrophilidae) species for the Turkish fauna, E. (E.) melanocephalus (Olivier, 1792) and E. (L.) fuscipennis (Thomson, 1884), are described, and their distribution in Turkey and worldwide is presented. A key to Turkish Enochrus species is provided and E. (L.) segmentinotatus treated under the "bicolor species complex". © Tübi?tak.
Keywords: Coleoptera; Enochrus; Hydrophilidae; Systematics; Turkey